1989
DOI: 10.1038/bjc.1989.143
|View full text |Cite
|
Sign up to set email alerts
|

Variations associated with the DNA analysis of multiple fine needle aspirates obtained from breast cancer patients

Abstract: Summary The present study was carried out to determine the variation in DNA content between multiple fine needle aspirates (FNA) of the same tumour from patients with breast cancer. Analysis of different aliquots of the same FNA showed good reproducibility in terms of cell cycle distribution and DNA index. Duplicate FNAs taken from different sites in nine of 11 excised tumours showed similar reproducibility. However, two of the aneuploid tumours displayed substantial variations in the distribution of cell popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The second addressed tumour heterogeneity and the representativity of sampling relative to the tumour mass. Repeated samplings were performed on seven patients, as already attempted by others (Mullen & Miller, 1989). Modifications of the DNA histograms were observed in four out of seven, consisting in variable representation of multiple DNA peaks.…”
Section: Methodsmentioning
confidence: 99%
“…The second addressed tumour heterogeneity and the representativity of sampling relative to the tumour mass. Repeated samplings were performed on seven patients, as already attempted by others (Mullen & Miller, 1989). Modifications of the DNA histograms were observed in four out of seven, consisting in variable representation of multiple DNA peaks.…”
Section: Methodsmentioning
confidence: 99%
“…In two cases (patients 17 and 18 in Table II (Prey et al, 1985;Erhardt & Auer, 1986;Remvikos et al, 1991) which have all shown good correlation between sequential FNAs from the same tumour. Only one study (Mullen & Miller, 1989) has commented on significant variation in DNA analysis caused by intratumoral heterogeneity between two fine-needle aspirates taken from the same tumour. Even here a com-parison of DI between two needle aspirates showed less than 5% variation in 10 out of 11 cases.…”
Section: Patientsmentioning
confidence: 99%
“…Sir -The letter from Dr Remvikos makes a number of criticisms of our paper (Mullen & Miller, 1989) which we feel are worth defending. With regard to the originality of the article and the possible omission of other work (Spyratos et al, 1987;Remvikos et al, 1988;Briffod et al, 1989), we feel our work is indeed original.…”
Section: Dna Flow Cytometry Of Breast Cancer Fine Needle Aspiratesmentioning
confidence: 99%
“…Sir -There are a number of points which I believe should be raised with regard to the article by Mullen and Miller (1989) on DNA flow cytometry of breast cancer fine needle aspirates. First, I would point out that the authors have omitted to reference previous contributions on the same topic (Spyratos et al, 1987;Remvikos et al, 1988a, Briffod et al, 1989.…”
Section: Dna Flow Cytometry Of Breast Cancer Fine Needle Aspiratesmentioning
confidence: 99%